PENGARUH SEMINAR ONLINE TERHADAP PENGETAHUAN DALAM MENINGKATKAN IMUNITAS UNTUK MENGHADAPI COVID-19 DAN PERSEPSI MENGENAI NEW NORMAL PADA MASYARAKAT AWAM - Mariatul Fadilah; Windi Indah Fajar Ningsih; Opel Berlin; Annisa Wimaulia; Azlin Azlin; Rizma Adlia Syakurah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
The government has issued a new normal policy with the aim that people can continue to live productively by changing their lifestyle so as to prevent the transmission of COVID-19. One of the measures to prevent and manage COVID-19 is to increase immunity. Online seminars are one of the most important health promotion methods and can be done in the new normal era. This study aims to determine the effect of online seminars on the knowledge and perceptions of the general public. This study used a quasi-experimental pre and post-test design. The sample in this study were all participants who attended online seminars and filled out the pretest and posttest questionnaires. Univariate data analysis shows that the majority of respondents have a mean age of 29.41 years, most of them are women (58.8%), and are students or have not worked (44.7%). Most of the respondents had a good level of initial knowledge about increasing immunity in the face of COVID-19 (68.4%) and a sufficient level of perception of the new normal (49.1%) before attending online seminars. The bivariate data analysis shows that there is a significant increase in knowledge about increasing immunity in the face of COVID-19 in the new normal before and after attending an online seminar with a p-value = 0.000 (p-value <0.05). Online seminars are the right way to promote health in increasing knowledge about immunity to deal with COVID-19 and perceptions of the new normal in ordinary people.